Recurrent myelitis and asymptomatic hypophysitis in IgG4-related disease: case-based review - Vakrakou, Aigli G.; Evangelopoulos, Maria-Eleptheria; Boutzios, Georgios; Tzanetakos, Dimitrios; Tzartos, John; Velonakis, Georgios; Toulas, Panagiotis; Anagnostouli, Maria; Andreadou, Elissavet; Koutsis, Georgios; Stefanis, Leonidas; Fragoulis, George E.; et al. (Rheumatology international, 2020)
IgG4-related disease (IgG4-RD) is a disorder with various clinical manifestations. Central nervous system (CNS) involvement is well recognized, with hypertrophic pachymeningitis and hypophysitis being the most common manifestations. Spinal cord involvement is an extremely rare manifestation. We present the first case of an IgG4-RD patient with spinal cord parenchymal disease and concurrent hypophysitis. We review also the current literature about CNS parenchymal involvement in the context of IgG4-RD. A young female presented with clinical symptoms of myelitis. Cervical spinal cord magnetic resonance imaging (MRI) displayed features of longitudinally extensive transverse myelitis (LETM). Brain MRI showed a small number of high-intensity lesions in the deep white matter and enlargement of hypophysis with homogeneous gadolinium enhancement (asymptomatic hypophysitis). Diagnostic workup revealed elevated IgG4 serum levels (146 mg/dL). Our patient fulfilled the organ-specific diagnostic criteria of IgG4-hypophysitis. Treatment with intravenous glucocorticoids led to rapid clinical response, and to the substantial resolution of imaging findings. Azathioprine was used as a maintenance treatment. One relapse occurred 2 years after the initial diagnosis and patient was re-treated with glucocorticoids. Three years after relapse, patient is in remission with azathioprine. We present the first case of myelitis with radiological features of LETM associated with increased IgG4 serum levels and the simultaneous presence of asymptomatic IgG4-related hypophysitis.